A Study on Customers’ Brand Preference of Selective Household Brands at Dindigul, Tamil Nadu - Venkateswaran, P. S.; Ananthi, N.; K., Binith Muthukrishnan (Indian Journal of Marketing, 2011)
In the middle of the twentieth century, customers had limited choice to select their brand or product. But by the end of the twentieth century, and at the beginning of the twenty first century, customers have a number of alternatives to select a single product. So, the current customers are having more brands to choose and thus, more conflicts/confusion arises due to it. This is a common nature for individuals. Within any product category, most consumers have a group of brand that comprises of their preference set. These are the four or five high-class brands the consumer will consider when making a purchase. In every product category, consumers have more choices, more information and higher expectations than ever before. To move consumers from trial to preference, brands need to deliver on their value proposition, as well as remove someone else from the consumer’s existing preference set. Corporates must know how the customers are going to prefer any specific brand among the alternatives in the market. If the corporates know the needs, wants and the preferences of the customers, then only they can reach the customers well in time. The present study tries to identify the factors which are influencing the customer’s satisfaction and preference to select a brand.